Empathy experiences of Japanese certified genetic counselors: A qualitative investigation and proposed framework. Issue 5 (21st April 2022) - Tomozawa, Chikako; Sasaki, Motoko; Kanbara, Yoko; Dong, Jingyi; Murakami, Haruka; Miyake, Hidehiko
Abstract: Empathy is an important element of genetic counseling. Most genetic counselors acknowledge the significance of empathically engaging clients. However, few empirical studies have focused on the empathy experience of genetic counselors, especially in non‐Western countries. This study aimed to investigate Japanese genetic counselors' perspectives on the concept of empathy in clinical practice. The study conducted semi‐structured interviews with Japanese certified genetic counselors who had approximately 10 years of clinical experience. Fourteen participants were interviewed about their thoughts on empathy and their experiences wherein they had deeply understood clients or felt closer to them. The interview data were analyzed using grounded theory. As a result, 17 categories were extracted, of which 13 were integrated into three themes of empathy: the empathic cycle in the relationships between genetic counselors and clients (cycling), the process of forming a deeper understanding of a client's perspectives (feeling), and the process of developing skills to understand clients with empathy (developing) . The remaining four categories were grouped into the theme of "challenges of empathy." The categories included in the first three themes were similar to previous findings in Western countries, whereas some categories of challenges of empathy were unique to this study, which was conducted in a non‐Western country. This might be attributed to the influence of Japanese culture, in which people emphasize self‐regulation and an interdependent‐self model. To our knowledge, this study is the first to report on Japanese certified genetic counselors' experiences of empathy. This study concludes with some suggestions for future research, including focusing on ways to overcome challenges of empathy in countries or healthcare systems.